Implementing Microsoft SharePoint 2019 : An Expert Guide to SharePoint Server for Architects, Administrators, and Developers. - Wanzer, Lewin; Wood, Angel (Birmingham : Packt Publishing, Limited, 2020)
SharePoint is one of Microsoft's most popular platforms and this book will cover the essentials such as governance, best practices, and configuration techniques that architects, developers, and administrators need to know to build robust infrastructure and server resources.
Table of ContentsUnderstanding Your Current StatePlanning and ArchitectureCreating and Managing Virtual MachinesInstallation ConceptsFarm and Services ConfigurationFinalizing the Farm -- Going LiveFinalizing the Farm to Go Live -- Part IIPost-Implementation Operations and MaintenanceManaging Performance and TroubleshootingSharePoint Advanced Reporting and FeaturesEnterprise Social Networking and CollaborationSharePoint Framework.
Description based upon print version of record.
eBooks on EBSCOhost
Keywords: Microsoft SharePoint (Electronic resource); Microsoft SharePoint (Electronic resource); Intranets (Computer networks); Web servers; Intranets; Serveurs Web; intranets; Collaboration & group software; Windows & variants; Microsoft programming; Computer networking & communications; Computers -- Programming -- Microsoft Programming; Computers -- Enterprise Applications -- Collaboration Software; Computers -- System Administration -- Windows Administration; Intranets (Computer networks); Web servers